Immunohistochemical expression of TGF-β1 and MMP-9 in periapical lesions - Pâmella Recco ÁLVARES; José Alcides Almeida de ARRUDA; Leorik Pereira da SILVA; George João Ferreira do NASCIMENTO; Maria Fonseca da SILVEIRA; Ana Paula Veras SOBRAL (Brazilian Oral Research, 2017)
Abstract The objective of this study was to evaluate the expression of matrix metalloproteinase 9 (MMP-9) and transforming growth factor beta (TGF-β1) in periapical lesion samples correlated with the intensity of the inflammatory infiltrate and thickness of the epithelial lining. Forty-five cases of periapical lesions (23 periapical granulomas and 22 radicular cysts) were subjected to morphological and immunohistochemical analyses using anti-MMP-9 and anti-TGF-β1 antibodies. The data were analyzed using the following tests: non-parametric Mann-Whitney, chi-square, Fisher’s exact test and Spearman’s correlation test (P<0.05). Analysis of inflammatory infiltrate revealed that 78% of periapical granulomas presented infiltrate grade III, in contrast with 32% of radicular cysts (P<0.001). Morphological evaluation of the epithelial thickness in radicular cysts revealed the presence of atrophic epithelium in 86% of the cysts. The immunostaining of MMP-9 was score 2 in 67% of the granulomas and 77% of the cysts. Both lesions were predominantly score 1 for TGF-β1. Significant differences were confirmed between the expression scores of TGF-β1 and MMP-9 in periapical granulomas (p = 0.004) and in radicular cysts (p < 0.001). Expression of TGF-β1 was different for periapical granulomas and radicular cysts. This immunoregulatory cytokine seems more representative in asymptomatic lesions. The extracellular matrix remodeling process dependent on MMP-9 seems to be similar for both periapical granulomas and radicular cysts. TGF-β1 and MMP-9 may play an important role in the maintenance of periapical lesions.